Pembelajaran Produktif Siswa UPT SMK Negeri 3 Muara Enim di Era Pandemi - Wahyuni, Najmi; Kristiawan, Muhammad (Yayasan Sembilan Pemuda Indonesia, 2021)
This study aims to see how efficient learning was implemented at SMK Negeri 3 Muara Enim during the Covid-19 era. Except for vocational students who will train with health procedures, learning is done online during the pandemic. This research employs qualitative approaches such as observational data collection, interviews, and documentation. Efficient teachers, curriculum waka, XII grade students, and student guardians served as study subjects. As a result, during the pandemic, efficient learning was implemented in two ways: online and by the use of the block method. This method of learning is relatively new because it can help students acquire a range of useful skills that are difficult to develop exclusively through online learning. Furthermore, some DU / DI host webinars with students on positive learning, which is particularly useful for students who are unable to practice in a business setting.